Rancang Bangun Aplikasi Aksi Sadar Keselamatan Jalan Berbasis Android - Mustaqbal, Zhilal Akbar; Pramesti, Meisya Nira; Mifta, Eka; Siswanto, Joko (UM Purwokerto Press, 2023)
High school students understanding of road safety regulations is still lacking causing traffic violations to increase among teenagers. This is due to the lack of road safety learning media. The android-based road safety action awareness application (SIAR SENJA) was built using app inventor software to increase understanding of road safety. SIAR SENJA application development uses the agile development method consisting of ideas, planning, development and evaluation. The SIAR SENJA application helps high school students understand road safety and be aware of the hazards involved, so that they can become pioneers of road safety in everyday life. SIAR SENJA application development can be done by adding animated video features and improving the display quality of the application.